Tailoring Built-In Electric Field in a Self-Assembled Zeolitic Imidazolate Framework/MXene Nanocomposites for Microwave Absorption - Gao, Zhenguo (Advanced materials (Deerfield Beach, Fla.), 2024)
© 2024 Wiley‐VCH GmbH.